Crystal Structures of 3,3′,5,5′-Tetrabromo-4,4′-bipyridine and Co(II) Coordination Polymer Based Thereon - Ilyas F. Sakhapov; Almaz A. Zagidullin; Alexey B. Dobrynin; Igor A. Litvinov; Dmitry G. Yakhvarov; Mikhail A. Bondarenko; Alexander S. Novikov; Vladimir P. Fedin; Sergey A. Adonin (Crystals, 2023)
The crystal structure of 3,3′,5,5′-tetrabromo-4,4′-bipyridine (BrBipy, 1) was determined, and the features of non-covalent interactions in solid state were investigated by theoretical methods. Using BrBipy as a linker ligand, 1D coordination polymer {[Co(BrBipy)(NO3)2(CH3OH)2]} (2) was obtained and characterized.